2013
DOI: 10.1016/j.jpsychires.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of affective with psychotic processes: A test of the effects of worrying on working memory, jumping to conclusions, and anomalies of experience in patients with persecutory delusions

Abstract: Worry has traditionally been considered in the study of common emotional disorders such as anxiety and depression, but recent studies indicate that worry may be a causal factor in the occurrence and persistence of persecutory delusions. The effect of worry on processes traditionally associated with psychosis has not been tested. The aim of the study was to examine the short-term effects of a bout of worry on three cognitive processes typically considered markers of psychosis: working memory, jumping to conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 55 publications
(31 reference statements)
4
28
1
Order By: Relevance
“…By contrast, the role of emotions in the development of DD is lacking, even though delusions appear to have a strong emotional component [20]; for instance, a vicious circle between cognitive biases and emotional disturbances may be involved in delusional patients [9]. Particularly, worry processing and rumination are associated with DLEs in healthy individuals [21] and increase anomalous experiences in delusional patients [22]. Therefore, in delusion phenomena "emotional processes must be given special consideration, even if their exact role is not well understood yet" [2].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the role of emotions in the development of DD is lacking, even though delusions appear to have a strong emotional component [20]; for instance, a vicious circle between cognitive biases and emotional disturbances may be involved in delusional patients [9]. Particularly, worry processing and rumination are associated with DLEs in healthy individuals [21] and increase anomalous experiences in delusional patients [22]. Therefore, in delusion phenomena "emotional processes must be given special consideration, even if their exact role is not well understood yet" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a longitudinal study of over 3000 participants in the UK found that childhood anxiety was a significant predictor of adult depersonalisation experiences [22]. Likewise, cognitive models of psychosis [23] emphasise the role of emotional processes, particularly anxiety, in the onset and maintenance cycle of psychotic symptoms [5, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…More severe perceptual anomalies, but not mild anomalies, reliably distinguished people with non‐clinical paranoia from people with persecutory delusions. In addition, worry was found to increase feelings of detachment from reality, increase perceptual alterations, and affect temporal disintegration (Freeman, Startup, et al, ). This suggests that increased worry may affect cognitive processing and may result in confusing perceptual experiences associated with paranoia.…”
Section: Resultsmentioning
confidence: 99%